Reaching for the Top: Advancing Women in Agriculture Research - Huyer, Sophia; Chanana, Nitya (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Global data demonstrates that women are less represented in agricultural research and advance at lower rates than men. A leaky pipeline effect diminishes the representation of women along the progression to senior manager and decision maker. In Africa, women make up only 25% of agricultural scientists , and a much lower proportion of decision makers on agriculture and climate at national and global levels. This InfoNote expands on the AICCRA case study on promoting women’s entry and advancement in agriculture and climate research, in terms of strategies to support women’s positive career experience and progression in AICCRA. It details the activities as well as the action points to monitor the activities.